Implementation strategies for effective change: a handbook for instructional leaders - Aistrup, Shelley A. (Kansas State University, 2010)
The purpose of this study was to research, develop, and validate a handbook of effective strategies that an instructional leader can implement and that are more likely to bring about and sustain a successful change process. Implementation Strategies for Effective Change: A Handbook for Instructional Leaders was developed using the research and development methodology as recommended by Gall, Borg, and Gall (1989, 1996) and Dick and Carey (1985) through a seven-step development cycle. The review of literature and proof of concept questionnaire provided information for developing the outline and initial prototype. Experts in the field served as preliminary field evaluators using a Likert scale and open-ended questions to provide feedback. Revisions were made based on their feedback. The main field test was conducted with potential users of the guide. Final revisions were based on main field test evaluators’ feedback. The conclusions of the study were: (1) the role of the principal has changed from that of a manager to an instructional leader who possesses a broad base of pedagogical and content knowledge and who understands how to lead a staff through a complicated change process; (2) a handbook that provides guidance and support for principals leading a change process focused on the improvement of instruction to raise student achievement would be a useful resource; (3) development of a comprehensive handbook or guide that blends theory, research, and practice for instructional leaders would be a beneficial resource; (4) the study produced a comprehensive guide to assist instructional leaders who are leading a change process focused on the improvement of instruction to raise student achievement, and (5) the strategies included in the handbook allow principals to adjust and adapt according to their schools’ unique situation and needs. The framework included in the comprehensive handbook provides strategies, tips, and suggestions for (1) developing leadership skills, (2) establishing the organizational structure within the school community, (3) building teachers’ knowledge base, and (4) fostering an understanding of the change process. Throughout the handbook, an emphasis is placed on the improvement of instruction to achieve high academic success for all students.
Keywords: Instructional leadership; Educational leadership; Educational reform; Change; Instructional practice; Student achievement; Education, Administration (0514)